2016
DOI: 10.1134/s0006297916070105
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogene PTENP1 functions as a competing endogenous RNA (ceRNA) to regulate PTEN expression by sponging miR-499-5p

Abstract: Increasing evidence has shown that pseudogenes can widely regulate gene expression. However, little is known about the specific role of PTENP1 and miR-499-5p in insulin resistance. The relative transcription level of PTENP1 was examined in db/db mice and high fat diet (HFD)-fed mice by real-time PCR. To explore the effect of PTENP1 on insulin resistance, adenovirus overexpressing or inhibiting vectors were injected through the tail vein. Bioinformatics predictions and a luciferase reporter assay were used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 18 publications
1
14
2
Order By: Relevance
“…Additionally, our data manifested that MT1H slightly affected the activation of RhoC-based signaling pathway and Cd-induced cell death through miR-214, suggesting a little contribution of MT1H to the activation of MT1DP/RhoC-CCN1/2-AKT pathway and resultant cell death outcome via miR-214. Although such a mutual ceRNA mechanism between protein-coding genes and their pseudogenes has not been extensively investigated, increasing evidence supports our finding on the reciprocal ceRNA mechanism between pseudogenes and their parental genes through competing for common miRNAs 43 , 73 such as cytochrome P450 family 2 subfamily A member 6 (CYP2A6) and its pseudogene CYP2A7 and phosphatase and tensin homolog deleted on chromosome ten (PTEN) and its pseudogene PTENP1 74 , 75 .…”
Section: Discussionsupporting
confidence: 83%
“…Additionally, our data manifested that MT1H slightly affected the activation of RhoC-based signaling pathway and Cd-induced cell death through miR-214, suggesting a little contribution of MT1H to the activation of MT1DP/RhoC-CCN1/2-AKT pathway and resultant cell death outcome via miR-214. Although such a mutual ceRNA mechanism between protein-coding genes and their pseudogenes has not been extensively investigated, increasing evidence supports our finding on the reciprocal ceRNA mechanism between pseudogenes and their parental genes through competing for common miRNAs 43 , 73 such as cytochrome P450 family 2 subfamily A member 6 (CYP2A6) and its pseudogene CYP2A7 and phosphatase and tensin homolog deleted on chromosome ten (PTEN) and its pseudogene PTENP1 74 , 75 .…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, we found that the overexpression of lentiviral‐mediated PTENP1 3′UTR significantly inhibited the proliferation of Eca109 and TE‐1 cells. It is known that PTENP1 expression could regulate the expression of PTEN . However, we only observed elevated expression of PTEN in Eca109 whereas no significant alteration was found in TE‐1 cell line.…”
Section: Discussioncontrasting
confidence: 68%
“…It is known that PTENP1 expression could regulate the expression of PTEN. 11,13,15,36 However, we only observed elevated expression of PTEN in Eca109 whereas no significant alteration was found in TE-1 cell line. This may be explained by the variation of the PTENP1 abundance and subcellular localization in different cell lines, which remains to be further validated.…”
Section: Discussioncontrasting
confidence: 61%
“…Studies have found PTENP1 to be lost or downregulated in various cancers [3, 5, 6, 8, 10, 11]. In ordert to evaluate PTENP1 status in GC, we determined the levels PTENP1 transcripts by qRT-PCR in 36 GC biopsies and their paired adjacent normal tissues from the same patients.…”
Section: Resultsmentioning
confidence: 99%